Antimicrobial Effect of Chitosan Nanoparticles on Streptococcus mutans Biofilms - Chávez de Paz, Luis E. (American Society for Microbiology, 2011)
Nanoparticle complexes were prepared from chitosans of various molecular weights (MW) and degrees of deacetylation (DD). The antimicrobial effect was assessed by the Live/Dead BacLight technique in conjunction with confocal scanning laser microscopy (CSLM) and image analysis. Nanocomplexes prepared from chitosans with high MW showed a low antimicrobial effect (20 to 25% of cells damaged), whereas those prepared from low-MW chitosans showed high antimicrobial effect (>95% of cells damaged).